Cloning of the Blue Ghost (Phausis reticulata) Luciferase Reveals a Glowing Source of Green Light1. (10th November 2016) - Branchini, Bruce R.; Southworth, Tara L.; Salituro, Leah J.; Fontaine, Danielle M.; Oba, Yuichi
Abstract: In the southern Appalachian area of the United States, the Phausis reticulata firefly, commonly known as the "Blue Ghost, " performs a unique display of bioluminescence. Adult male organisms are observed darting rapidly along paths and riverbeds in dark forests producing long‐lasting and mesmerizing bluish‐white luminous streaks. Starting with eighteen adult male firefly lanterns, we used a reverse transcriptase and rapid amplification of cDNA ends (RACE) approach to clone the 1635 base pair open reading frame of the P. reticulata luc gene corresponding to a 545 residue protein. Expression of the recombinant luciferase protein in Escherichia coli and characterization studies revealed the true color of the light emission to be green ( λ max = 552 nm), strongly suggesting that the field observations result from a Purkinje shift. While the P. reticulata luciferase amino acid sequence is 74.3% identical to the North American Photinus pyralis luciferase, we were surprised to find that it was 88.4% and 87.7% identical to luciferases from C . ruficollis and D. axillaris both native to mainland Japan. Phylogenetic analysis confirmed the close relationship of the three enzymes that is surprising given the great distance between their natural habitats and the inability of the Japanese fireflies to produce bright bioluminescence. Abstract : This time‐lapse photograph by Spencer Black (Blackvisual.com) entitled "Searching for Love" is a beautiful illustration of the mysterious Blue Ghost ( Phausis reticulata ) fireflies on a summer night in North Carolina. We recently witnessed this fascinating natural display in the Dupont State Recreational Forest while collecting several adult males. Using tiny lanterns from 18 specimens, we cloned the Blue Ghost luciferase gene and then studied the properties of the corresponding enzyme. We offer an explanation for the mesmerizing bluish‐white color of the luminous streaks and report the puzzling similarity of the luciferase to that of fireflies found only in Japan.